Apakah Pembelajaran Menggunakan Teknologi dapat Meningkatkan Literasi Manusia pada Generasi Z di Indonesia? (Jurnal Manajemen Informatika (JAMIKA), 2020)
Learning methods using technology such as e-learning, online-learning or blended learning have begun to be applied. In the context of facing the 4.0 Indonesian Revolution, Indonesia is trying to improve three new literacies, namely technology literacy to understand the workings of machines, technology applications (Coding / Programming, Artificial Intelligence & Engineering Principles), data literacy for reading, analyzing, and using information (Big Data) in the digital world and human literacy for communication skills, collaboration, critical thinking, creative and innovative as well as having leadership skills, team work and so on. The Ministry of Higher Education (Dikti) also launched the Indonesian Online Learning System (SPADA) to improve access to quality higher education in Indonesia. Generation Z is the generation currently in tertiary education, so they automatically become the main target in the implementation of SPADA and the increase in the three literacies. Generation Z has certain characteristics that are different from other generations. This literature review research aims to find out whether the application of learning by using technology can increase or even lower human literacy in Generation Z in Indonesia. The method used in this research is literature review. The results show that the use of technology in learning is still difficult to be able to increase human literacy in Generation Z because they tend to have difficulty communicating directly, instantly and fading cultural and religious values.